2022
DOI: 10.3727/152599521x16192004803656
|View full text |Cite
|
Sign up to set email alerts
|

Audience Diversity and Well-being at Uk Drag Events

Abstract: Over the last 15 years, there has been a significant increase in the promotion and integration of drag culture into mainstream society. Drag events have the ability to create a safe place for people from diverse backgrounds to celebrate and gather. What were once underground expressions of gender and political protest for the LGBTQ+ (lesbian, gay, bisexual, transgender, queer plus other identities) community, drag events have now transcended into a modern-day phenomenon, bringing people together to participate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…These spaces are open for those who feel part of the community or support the community, yet this poses its own problems. As Baxter et al (2022)…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…These spaces are open for those who feel part of the community or support the community, yet this poses its own problems. As Baxter et al (2022)…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Cisneros and Bracho (2020), some spaces can feel safe for members of particular groups (based on gender, sexuality, race, class, and age), but unsafe for others. Baxter et al (2022) alluded to there being a feeling within the LGBTQþ community that their safe spaces were now changing due to a shift in the demographic attending and suggested that this was making them feel unsafe. Myslik (1996) found that feeling safe is the emotional and psychological safety that comes from being in a space in which one has some sense of belonging or social control.…”
Section: Highlight Thementioning
confidence: 99%
See 3 more Smart Citations